Radiological Findings of Extramedullary Haematopoiesis of Spleen in Beta Thalassaemia Major: A Case Report - Soumyabrata Debnath; Pulkit Kumar Santoshi; Monali Debnath (Journal of Clinical and Diagnostic Research, 2024)
Extramedullary Haematopoiesis (EMH) is a compensatory response occurring secondary to inadequate bone marrow function and is observed in many haematological conditions. EMH can occur in many haemoglobinopathies. Extramedullary haemopoiesis favours certain sites such as the liver, the spleen, and the paraspinal regions of the thorax. However, in addition to these common sites of extramedullary haemopoiesis, the process can involve virtually any organ or tissue and can often manifest as a mass mimicking a neoplasm. Although EMH is usually asymptomatic, clinical symptoms can appear due to mass effect. Radiological evaluation can be done using Ultrasonography (USG), Computed Tomography (CT) scan, and T2, T1 weighted Magnetic Resonance Imaging (MRI). Both conservative and surgical treatments are practiced depending on the organ involvement. Here, is a rare case of a young female in her mid-20s, who was a known case of beta thalassaemia major. She presented with a mass insidiously growing in left flank region, which on radiological imaging was found to be focal mass in the spleen. The pathological diagnosis after elective splenectomy was EMH of spleen. Due to chronic transfusions in patients of beta thalassaemia major, EMH is rarely seen. In-fact, the incidence of EMH in beta-thalassaemia major is thought to be less than 1%, which makes the present case a rare entity.